Comparative Study of Proactivators of the Fibrinolysin System in Three Mammalian Species - Takada, Y; Takada, A; Ambrus, J. L (Thrombosis and Haemostasis, 1969)
Sephadex gel filtration of human plasma gave results suggesting the presence of two proactivators of plasminogen, termed proactivators A and B.Activity resembling that of proactivator A was found in rabbit plasma, but not in guinea pig plasma.Plasminogen activators produced by the interaction of proactivator A of human plasma with streptokinase had no caseinolytic or TAMe esterolytic effect.Proactivator A can be separated in a form apparently free from plasminogen, as shown by the heated fibrin plate test and by immunological analysis. On the other hand, proactivator B concentrates prepared so far are contamined with plasminogen.Human proactivators appear to be far more susceptible to streptokinase than are rabbit proactivators.Inhibitors of the fibrinolysin system were observed in the plasmas of all 3 species. These inhibitors are not present in the euglobulin fraction of plasma. Sephadex fractionation of euglobulin fractions results in proactivator preparations that do not contain inhibitors.